2008
DOI: 10.1590/s1806-83242008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of human and bovine teeth: radiographic density

Abstract: Since bovine teeth have been used as substitutes for human teeth in in vitro dental studies, the aim of this study was to compare the radiographic density of bovine teeth with that of human teeth to evaluate their usability for radiographic studies. Thirty bovine and twenty human teeth were cut transversally in 1 millimeter-thick slices. The slices were X-rayed using a digital radiographic system and an intraoral X-ray machine at 65 kVp and 7 mA. The exposure time (0.08 s) and the target-sensor distance (40 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 10 publications
0
41
0
5
Order By: Relevance
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
“…Tanaka et al (47) found that the radiographic density of bovine enamel and coronal dentin was significantly higher than that of human enamel and coronal dentin, respectively. However, no significant difference in the …”
Section: Physical Properties Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…colhida pela maioria dos pesquisadores, uma vez que são facilmente obtidos e cada vez mais indicados pelos comitês de ética (Seixas et al 2007, Matos et al 2008, Tanaka et al 2008. O Brasil possui o maior rebanho de búfalos das Américas, com a criação em grande escala direcionada para a produção de carne, restando uma alta disponibilidade de material biológico para outros fins, como os estudos científicos (Santana et al 2011).…”
unclassified
“…A princípio, a composição química e estrutural do esmalte de todos os mamíferos é igual, porém pode haver alguma variação dependendo da espécie do animal (MORIWAKI et al, 1968). Os dentes bovinos são comumente utilizados em estudos laboratoriais por não possuírem restrições éticas, serem mais facilmente obtidos que os humanos e possuírem tamanho amplo (TANAKA et al, 2008). Estudos demonstraram que apesar de ser mais poroso que o humano (MORIWAKI et al, 1968;MELLBERG, 1992), o dente bovino possui composição mais uniforme (MELLBERG, 1992), podendo produzir resposta aos desafios cariogênicos com menor variação MELLBERG, 1981).…”
Section: Introductionunclassified